2019
DOI: 10.1080/21645515.2019.1606972
|View full text |Cite
|
Sign up to set email alerts
|

Classical and novel strategies to develop aShigellaglycoconjugate vaccine: from concept to efficacy in human

Abstract: Shigella are gram-negative bacteria that cause severe diarrhea and dysentery, with a high level of antimicrobial resistance. Disease-induced protection against reinfection in Shigella -endemic areas provides convincing evidence on the feasibility of a vaccine and on the importance of Shigella lipopolysaccharides as targets of the host humoral protective immune response against disease. This article provides an overview of the original and current strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 119 publications
3
69
1
Order By: Relevance
“…Live attenuated strains such as S. dysenteriae type 1 WRSd1, S. sonnei WRSS1, WRSs2, WRSs3, and some whole-cell-killed and novel antigen candidates are now developing, and were safe and immunogenic in a phase I trial (more details are presented in Table 3). Among possible Shigella candidate vaccines, GMMA protein particles, live attenuated Shigella flexneri 2a SC602, and S. dysenteriae type 1 SC599 strains have entered phase II clinical evaluation, and only glycoconjugate candidates have already undergone Phase III trials, with other formulations still under development in patients with shigellosis 192,193. As shown in Table 3, many studies have demonstrated humoral response as a main value of an immunoresponse to vaccination, and also fever and transient diarrhea have been repaorted as the most frequent complications in relation to some vaccine candidates in clinical investigations (Table 3).…”
Section: Novel Therapeutic Strategies For Shigella Treatmentmentioning
confidence: 99%
“…Live attenuated strains such as S. dysenteriae type 1 WRSd1, S. sonnei WRSS1, WRSs2, WRSs3, and some whole-cell-killed and novel antigen candidates are now developing, and were safe and immunogenic in a phase I trial (more details are presented in Table 3). Among possible Shigella candidate vaccines, GMMA protein particles, live attenuated Shigella flexneri 2a SC602, and S. dysenteriae type 1 SC599 strains have entered phase II clinical evaluation, and only glycoconjugate candidates have already undergone Phase III trials, with other formulations still under development in patients with shigellosis 192,193. As shown in Table 3, many studies have demonstrated humoral response as a main value of an immunoresponse to vaccination, and also fever and transient diarrhea have been repaorted as the most frequent complications in relation to some vaccine candidates in clinical investigations (Table 3).…”
Section: Novel Therapeutic Strategies For Shigella Treatmentmentioning
confidence: 99%
“…As study case we focus on carbohydrates, a class of molecules for which the stereochemistry and the high degree of functionalization are key reactivity factors. Carbohydrate chemistry is essential for accessing complex glycans that are used as tool compounds to investigate fundamental biological processes such as protein glycosylation 27 – 29 , as well as for the preparation of synthetic vaccines 30 32 . Predicting the outcome of carbohydrate transformations, such as regioselective protection/deprotection of multiple hydroxyl groups or the stereospecificity of glycosylation reactions, is a very difficult task even for experienced carbohydrate chemists 33 , 34 , implying that this field of research might particularly benefit from computer-assisted reaction prediction tools.…”
Section: Introductionmentioning
confidence: 99%
“…Bioconjugates are finally released to outer membrane after cell lysis. 153 Bioconjugate vaccine candidates for S. dysenteriae (SD133) and S. flexneri 2a (Flexyn2a) were demonstrated safe and immunogenic in phase I trials. 154,155 Well-defined synthetic oligosaccharides were investigated as Shigella O-antigen surrogates to improve conjugate vaccine candidacy.…”
Section: Polysaccharide-based Subunit Vaccine Candidatesmentioning
confidence: 99%
“…157 However, the feasibility of using synthetic O-antigen surrogates in developing Shigella vaccines is yet to be fully established. 153 Additionally, S. sonnei 1790GAHB GMMA (generalized modules for membrane antigens) vaccine, blebs or native outer membrane vesicles shed by a genetically modified S. sonnei strain for a high level of production of LPS blebs, 158 was generally safe and induced robust antibody response to S. sonnei LPS in adults from an Africa endemic country. 159 Since Shigella O-antigen moieties of LPS are diverse due to variations of repeating units (two to six monosaccharides) thus are serotype specific, anti-LPS antibodies derived from an O-antigen of one Shigella serotype protect against homologous infections but cannot provide cross-protection against heterogeneous serotypes.…”
Section: Polysaccharide-based Subunit Vaccine Candidatesmentioning
confidence: 99%